Creative Approaches in History Teaching: Methodological Solutions Based on Triz - Ergashev Bakhodir Olimjon o‘g‘li (Scientific Trends, 2025)
This article is dedicated to fostering creative approaches in history teaching, analyzing methodological solutions based on the TRIZ (Theory of Inventive Problem Solving) methodology from a scientific perspective. The introduction discusses the challenges of traditional education and the role of TRIZ in the educational process, while the main body examines specific examples of analyzing historical events through TRIZ principles, their application in the humanities, and their adaptation to the Uzbekistan education system. The conclusion highlights the advantages, impact, and future prospects of integrating TRIZ. Grounded in modern trends in Uzbekistan’s pedagogy and incorporating international research findings, the study aims to contribute to developing students’ creative thinking and problem-solving skills while proposing ways to enhance educational quality.
Keywords: TRIZ, history teaching, creative approaches, methodological solutions, creative thinking, humanities, pedagogical innovations, problem-solving, educational technologies, Uzbekistan education.